Fat phobia: existence of a denied body. Analysis of subjective implications of the fat body in modern society - Quirós Sánchez, Gabriela (2021)
The present manuscript is intended to encourage reflection on the social construction of fat body, from analysis of fatphobia as an element of psychosocial learning that aims at categorization of bodies, promoting a differentiated positioning for people whose bodys are not determined within rigid structures of current body aesthetic. Learning about the body has different effects on people’s lives. The gender construction, social learning and family´s legitimization of discriminatory discourse is some of the mechanisms by which fat-phobia permeates bodily self-perception and influences the way we treat and interact with each other. Recognizing Latin American body diversity not only has to do with recognizing the forms of our bodies, but also has to do with recognizing and accepting the historical heritage of our blending. This is a pending claim by fashion influence, the market and the heteropatriarchal look on the body.